2007
DOI: 10.1111/j.1752-1688.2007.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Five Hundred Years of Hydrological Drought in the Upper Colorado River Basin1

Abstract: This article evaluates drought scenarios of the Upper Colorado River basin (UCRB) considering multiple drought variables for the past 500 years and positions the current drought in terms of the magnitude and frequency. Drought characteristics were developed considering water‐year data of UCRB’s streamflow, and basin‐wide averages of the Palmer Hydrological Drought Index (PHDI) and the Palmer Z Index. Streamflow and drought indices were reconstructed for the last 500 years using a principal component regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Guttman et al (1992) and Alley (1985) reported that PDSI depicted spatially does not identify areas of equal hydrologic drought intensity owing to the variability of precipitation and groundwater levels over large areas. It suggests that PDSI, Palmer hydrologic drought index (PHDI), and streamflow and their relationship to climate signals such as El Niño-Southern Oscillation (ENSO) provides only a broad framework for regional hydrologic drought dynamics (Piechota and Dracup 1996;Timilsena et al 2007;Tsakiris and Vangelis 2004). Therefore, an approach that is fundamentally linked to soil moisture and its measurement in the vadose zone, can only serve to enhance our ability to quantify local drought, especially during the crop-growing season, for the obvious linkages with evapotranspiration, precipitation, and deep soil moisture as reported in many studies (e.g., Sandvig and Phillips 2006;Hong and Kalnay 2000;Sheffield et al 2004;Entekhabi et al 1992;Koster et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Guttman et al (1992) and Alley (1985) reported that PDSI depicted spatially does not identify areas of equal hydrologic drought intensity owing to the variability of precipitation and groundwater levels over large areas. It suggests that PDSI, Palmer hydrologic drought index (PHDI), and streamflow and their relationship to climate signals such as El Niño-Southern Oscillation (ENSO) provides only a broad framework for regional hydrologic drought dynamics (Piechota and Dracup 1996;Timilsena et al 2007;Tsakiris and Vangelis 2004). Therefore, an approach that is fundamentally linked to soil moisture and its measurement in the vadose zone, can only serve to enhance our ability to quantify local drought, especially during the crop-growing season, for the obvious linkages with evapotranspiration, precipitation, and deep soil moisture as reported in many studies (e.g., Sandvig and Phillips 2006;Hong and Kalnay 2000;Sheffield et al 2004;Entekhabi et al 1992;Koster et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…From 2000 through 2010, the Colorado River Basin has experienced the driest period on record and one the worst droughts in history (e.g, Timilsena et al, 2007). At the beginning of water year 1999 (October 1998), water storage in the Colorado River Basin was at 94 % capacity; in particular, the two largest reservoirs within the system, Lake Powell and Lake Mead, were at 98 % and 91 % capacity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the term "intensity" (ratio of severity to duration) has been used interchangeably with magnitude (Dracup et al, 1980;Panu & Sharma, 2002). Use of the term magnitude in the hydrological drought context seems to be gaining momentum (Timilsena et al, 2007;Lopez-Moreno et al, 2009). In view of the changing trend in the nomenclature of drought parameters, the term magnitude shall be used in place of severity, and the ratio of magnitude to duration shall be termed drought intensity in this study.…”
Section: Introductionmentioning
confidence: 99%